Faktor-Faktor yang Mempengaruhi Implementasi Kebijakan Publik di Sektor Pertanian: Suatu Tinjauan Literatur - Hermawan, Susong; Rusli, Budiman; Darto, Darto (Jurnal Ilmiah Administrasi Publik, 2025)
This article reviews various forms of public policies in the agricultural sector that have been implemented, along with the factors influencing their implementation in several regions of Indonesia. Referring to the provisions stipulated in Pasal 23 Ayat 1 of Undang-Undang Nomor 6 Tahun 2023, the central and regional governments, in accordance with their respective authorities, are mandated to sustainably increase productivity in the agricultural sector to achieve food security. Based on the literature review, the forms of public policies implemented by the government include: (1) Food estate, (2) Kostratani, (3) LP2B, (4) AUTP, (5) Subsidized fertilizers, and (6) Millennial farmer programs. The factors influencing the implementation process are: (1) communication, (2) interests, (3) socialization, (4) resources, and (5) the environment. It is recommended that future policy formulation processes prioritize analysis based on regional suitability, strengthen communication between stakeholders through socialization efforts, focus group discussions (FGDs), and public hearings, improve the quality and quantity of implementing human resources, and provide training and guidance for target groups (farmers) to enhance their understanding and perceptions.